TikTok as a Learning Media for Islamic Religious Education for the Millennial Generation (Case Study at Dinamika University, Surabaya) - Muvid, Muhamad Basyrul; Sahibuddin, M; Masiroh, Siti; Isroiyah, Isroiyah (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The development of technology is increasing rapidly, TikTok social media is one of the trending media, so it has a significant influence on the younger generation. The purpose of this study is how TikTok becomes a medium of PAI learning for the younger generation, especially in universities, which hopes to help the effectiveness of student learning, provide new experiences, and new knowledge and be able to provide confidence to students in expression, discussion and questions and answers on TikTok. The research method used is qualitative with a case study approach, namely at Dinamika University Surabaya, with the object of research being students who take Islamic Religion classes, data collection techniques using observation, interviews, and documentation, then data analysis techniques using induction and interpretation. The results found are that TikTok can be used as a medium for teaching Islamic religious education for students, because it has an impact on the effectiveness of learning in the classroom, students are given flexibility in exploring so that they can be more extensive in providing responses, views, questions and answers and conclusions on the material being discussed, of course still with the supervision and control of the lecturer so that the substance of the material can stay on track not to get out of the proper path. TikTok media provides a wider opportunity for students to learn and discuss, experience and competence.